A MCo2O4@MoS2 / RGO electrode material and its preparation method and application
By synthesizing core-shell MCo2O4 nano microspheres on MoS2/RGO substrate and forming a "sesame ball"-like structure, the problems of low specific capacity and easy agglomeration of existing electrode materials are solved, and high specific capacitance and excellent electrochemical performance are achieved.
Patent Information
- Application Number
- CN202211151690.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-21
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2042-09-21
AI Technical Summary
The existing supercapacitor electrode materials have problems such as low specific capacity and easy agglomeration, which limits their application in the field of energy storage.
Using MCo2O4@MoS2/RGO electrode material, core-shell MCo2O4 nano microspheres were synthesized in situ on the MoS2/RGO substrate, and some MoS2 were redistributed on the surface of MCo2O4 nano microspheres during the synthesis process to form a "sesame sphere"-like structure.
The specific capacitance of the electrode material has been significantly improved to reach 1000F g-1, solving the agglomeration problem, increasing the specific surface area and electrochemical activity of the material, and improving the energy storage capacity.
Smart Images

Figure CN115831622B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrode material preparation, and specifically relates to a MCo2O4@MoS2 / RGO electrode material and a preparation method and application thereof. Background Art
[0002] Due to the increasing shortage of fossil energy and environmental pollution caused by combustion emissions, and the current advocacy of a "green" and "low-carbon" economic development model, the development of renewable energy is particularly urgent. Supercapacitors are one of the most promising energy storage devices for electronic devices and hybrid vehicles due to their high energy density, power density, and long cycle life. The performance of supercapacitors is closely related to electrode materials. Therefore, it is necessary to develop electrode materials with high specific capacitance, high energy density, longer cycle life, lower cost, and better safety performance.
[0003] Graphene is a two-dimensional conjugated graphite structure with excellent electrical, mechanical and optical properties, as well as high conductivity and large specific surface area. It has potential value in improving the energy density of supercapacitors. Although graphene is an ideal capacitor electrode material, it still has problems such as low specific capacity and easy agglomeration. A large amount of agglomerated graphene not only limits the transmission of charge, but also significantly reduces the effective area of charge conduction and storage, which limits its use in supercapacitors.
[0004] MoS2 has attracted wide attention due to its unique two-dimensional structure and high specific surface area. Compared with graphene, MoS2 nanosheets can store energy in the two-dimensional channels between nanosheets, which is conducive to the rapid transfer of ions and free expansion and contraction. In addition, MoS2 nanosheets also have potential promising properties such as good mechanical properties, high packing density and flexibility, making them suitable for the development of flexible, thin, all-solid-state supercapacitors and micro-supercapacitors. However, MoS2 has low conductivity as a supercapacitor anode, which limits its application in the field of energy storage.
[0005] In the prior art, graphene and MoS2 are compounded and self-assembled by electrostatic adsorption to obtain an electrode material having a layered structure of a single layer or a few layers of graphene and a single layer of molybdenum disulfide, or a binary mixed molybdenum cobalt sulfide nanosheet is modified on reduced graphene oxide as a high-performance supercapacitor electrode. However, binary materials still have performance limitations and agglomeration problems between materials. Summary of the invention
[0006] In view of the shortcomings in the prior art, the present invention provides a MCo2O4@MoS2 / RGO electrode material and a preparation method and application thereof. In the present invention, MoS2 and RGO are firstly compounded to prepare MoS2 / RGO, and then MoS2 / RGO and MCo2O4 (M includes any one of Mn, Ni, Mg, Cu, and Zn) are compounded to prepare MCo2O4@MoS2 / RGO electrode material; the preparation method of the MCo2O4@MoS2 / RGO electrode material is simple, efficient, and low-cost, and the prepared electrode material is of high quality, and has good application prospects in the fields of micro-nanoelectronic devices, solar cell electrodes, photoelectric converters, transparent conductive films, etc.
[0007] The present invention first provides an MCo2O4@MoS2 / RGO electrode material, in which MoS2 / RGO is used as a substrate, and core-shell MCo2O4 nano-microspheres are in situ synthesized on the MoS2 / RGO substrate; in the MCo2O4@MoS2 / RGO electrode material, MoS2 nanoflowers grow between RGO sheets, and core-shell MCo2O4 nano-microspheres are uniformly dispersed between MoS2 / RGO sheets, wherein M includes any one of Mn, Ni, Mg, Cu, and Zn.
[0008] Furthermore, when core-shell MCo2O4 nanospheres were in situ synthesized on MoS2 / RGO, part of the MoS2 was redistributed on the surface of the MCo2O4 nanospheres, making the MCo2O4@MoS2 / RGO electrode material sesame-shaped.
[0009] The present invention also provides a method for preparing the MCo2O4@MoS2 / RGO electrode material, which specifically comprises the following steps:
[0010] (1) Preparation of GO:
[0011] Concentrated H2SO4 and H3PO4 were stirred and mixed evenly, graphite powder was added and mixed evenly, and then KMnO4 was added in batches, and the mixture was stirred and reacted in an ice-water bath. After the reaction was completed, a reaction solution was obtained, and deionized water and H2O2 were added to the reaction solution. The reaction solution turned yellow-brown and a precipitate was obtained. The precipitate was washed and dried to obtain GO.
[0012] (2) Preparation of MoS2 / RGO:
[0013] GO was ultrasonically dispersed in deionized water, and then a surfactant aqueous solution, MoO3 and KSCN were added thereto, and the mixture was stirred and evenly mixed before a hydrothermal reaction was performed. After the reaction was completed, a precipitate was obtained, which was washed and dried to obtain MoS2 / RGO;
[0014] (3) Preparation of MCo2O4@MoS2 / RGO electrode materials:
[0015] MoS2 / RGO was dispersed in deionized water, and then nitrate, Co(NO)3·6H2O, d-glucose and urea were added in sequence, stirred and mixed evenly, and then subjected to hydrothermal reaction. After the reaction, a precipitate was obtained, washed and dried to obtain MCo2O4@MoS2 / RGO electrode material.
[0016] Further, in step (1), the ratio of concentrated H2SO4, H3PO4, graphite powder, KMnO4, deionized water and H2O2 is 12mL: 1mL: 1g: 1g: 200ml: 9ml-1mL: 1mL: 5g: 8g: 300mL: 5mL; wherein the concentration of H2O2 is 8-11mol / L;
[0017] The stirring reaction condition is 20-26h.
[0018] Furthermore, in step (2), the ratio of GO, deionized water, surfactant, MoO3 and KSCN is 0.01-0.04 g: 40-80 mL: 3-5 mmol: 1.5-3 mmol: 0.4-0.5 mmol;
[0019] The surfactant includes any one of sodium dodecylbenzene sulfonate, sodium tetrapropylenebenzene sulfonate, sodium diisooctyl sulfosuccinate, and sodium dibutylnaphthalene sulfonate;
[0020] The hydrothermal reaction conditions are 190-240° C. for 16-26 hours.
[0021] Further, in step (3), the amount ratio of MoS2 / RGO, deionized water, nitrate, Co(NO)3·6H2O, d-glucose and urea is: 10-100 mg: 50-100 mL: 1-4 mmol: 1-5 mmol: 1-10 g: 3.5-9.5 mmol;
[0022] The nitrate includes any one of Mn(NO)2·6H2O, Ni(NO)2·6H2O, Mg(NO)2·6H2O, Cu(NO)2·6H2O, and Zn(NO)2·6H2O;
[0023] The hydrothermal reaction conditions are 190-240° C. for 12-24 hours.
[0024] The present invention also provides the use of the above-mentioned MCo2O4@MoS2 / RGO electrode material in the preparation of supercapacitors.
[0025] The MCo2O4@MoS2 / RGO electrode material of the present invention can also be applied to micro-nano electronic devices, solar cell electrodes, photoelectric converters, and transparent conductive films.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] In the present invention, MoS2 and RGO composite are selected as the substrate, and MoS2 is intercalated between RGO sheets, which solves the problem of graphene agglomeration. The intercalation of MoS2 facilitates the rapid transmission, free expansion and contraction of ions, and the volume does not change significantly. The present invention also synthesizes core-shell MCo2O4 nano-microspheres in situ on the MoS2 / RGO substrate, which solves the agglomeration problem of synthesizing MCo2O4 in the past. MCo2O4 is evenly dispersed between the sheets, further reducing the agglomeration of MoS2 and RGO, increasing the interlamellar spacing, and providing a larger contact interface for the core-shell MCo2O4 nano-microspheres, ensuring sufficient close contact between the composite materials. In addition, in the process of synthesizing core-shell MCo2O4 nano-microspheres on the MoS2 / RGO substrate, part of MoS2 is redistributed on the surface of MCo2O4 nano-microspheres to form a ternary electrode material with a "sesame ball" structure. MCo2O4 nano-microspheres are added on the basis of MoS2 / RGO to form a conductive network-like ternary electrode material, and the materials work synergistically to improve the energy storage capacity of the electrode material.
[0028] In the present invention, cobaltates with a core-shell structure are selected to prepare MCo2O4@MoS2 / RGO electrode materials. The cobaltates with a core-shell structure have abundant surface area and can provide more active sites for chemical reactions. The nanoshell of MCo2O4 in the MCo2O4@MoS2 / RGO electrode material can increase the chance of the active substance contacting the electrolyte during the electrochemical process. The hollow structure provides an electrolyte ion buffer reservoir for the electrode material. Compounding with other materials can significantly improve the electrochemical performance of the composite material.
[0029] The "sesame ball"-shaped MCo2O4 nanospheres prepared by the present invention have stronger electronic interactions and abundant active surface areas, providing abundant channels for chemical reactions. The hollow structure provides an electrolyte ion buffer for the electrode material, which is more conducive to the transfer and transportation of electrolyte ions. The synergistic effect between the multi-element metal compound MCo2O4 and MoS2 / RGO is conducive to improving the conductivity of the electrode material, increasing the diffusion rate of the reactants, and accelerating the charge transfer. The composite material exhibits excellent electrochemical properties. Compared with the prior art, the graphene specific capacitance can reach 100F g -1 After adding MoS2, the specific capacitance is increased to 300F g -1 The MCo2O4@MoS2 / RGO electrode material described in the present invention has a specific capacitance of up to 1000Fg-1 , significantly improving the specific capacitance of electrode materials.
[0030] The preparation method of the hydrothermally synthesized MCo2O4@MoS2 / RGO electrode material of the present invention is simple, efficient and low-cost. The prepared electrode material is of high quality and has good application prospects in the fields of micro-nano electronic devices, solar cell electrodes, photoelectric converters, transparent conductive films, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a scanning electron microscope image of MCo2O4@MoS2 / RGO electrode material.
[0032] Figure 2 This is the Raman spectrum of MCo2O4@MoS2 / RGO electrode material.
[0033] Figure 3 This is the transmission electron microscope image of MCo2O4@MoS2 / RGO electrode material.
[0034] Figure 4 This is the electrochemical test results of MCo2O4@MoS2 / RGO electrode material. DETAILED DESCRIPTION
[0035] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto.
[0036] Embodiment 1:
[0037] (1) Preparation of GO:
[0038] Add 200mL of concentrated H2SO4 and 20mL of H3PO4 into the reactor and stir for 20min to mix evenly. Then add 1g of graphite powder and add 6g of KMnO4 in batches. Stir and react for 24h in an ice-water bath. After the reaction, add 250mL of deionized water below 5°C to the reaction solution and then add 0.03mol of H2O2. The color of the reaction solution instantly turns yellow-brown and a precipitate is obtained. Wash with distilled water and freeze-dry for 10h to obtain GO.
[0039] (2) Preparation of MoS2 / RGO:
[0040] Take 20 mg of GO and ultrasonically disperse it in 60 mL of deionized water. Then, add an aqueous solution containing 4 mmol of sodium dodecylbenzene sulfonate, 2.5 mmol of MoO3 and 0.46 mmol of KSCN and stir for 20 min. Then, in a high-pressure reactor, react the mixed solution at 220 ° C for 24 h to obtain a precipitate. The precipitate is then washed with deionized water and freeze-dried for 10 h to obtain MoS2 / RGO.
[0041] (3) Preparation of NiCo2O4@MoS2 / RGO electrode materials:
[0042] 50 mg MoS2 / RGO was ultrasonically dispersed in 60 mL deionized water, and then 2.4 mmol Ni(NO)2·6H2O, 3 mmol Co(NO)3·6H2O, 6 g d-glucose and 7.2 mmol urea were added thereto in sequence. After stirring and mixing evenly, the mixture was hydrothermally reacted at 220 °C for 18 h. After the reaction, a precipitate was obtained, which was washed and dried to obtain MCo2O4@MoS2 / RGO electrode material.
[0043] Figure 1 This is a scanning electron microscope image of the NiCo2O4@MoS2 / RGO electrode material. It can be seen from the figure that GO is an ultra-thin two-dimensional sheet structure, which is evenly dispersed as a substrate. The curved MoS2 nanosheets between the GO sheets grow vertically to form MoS2 nanoflowers, increasing the spacing between the RGO sheets and reducing RGO agglomeration. The "sesame ball"-shaped NiCo2O4 nano-microspheres are intercalated between the single-layer RGO sheets, with uniform shapes and sizes, solving the agglomeration problem.
[0044] Figure 2 This is the Raman spectrum of NiCo2O4@MoS2 / RGO electrode material. It can be seen from the figure that there are characteristic peaks of NiCo2O4, MoS2 and RGO, which illustrates the successful preparation of NiCo2O4@MoS2 / RGO electrode material.
[0045] Figure 3 This is a transmission electron microscope image of the NiCo2O4@MoS2 / RGO electrode material. It can be seen from the image that RGO is in the form of wrinkled sheets, and the nano-flower-like MoS2 is evenly distributed on the RGO sheets without agglomeration. The NiCo2O4 core-shell structure is hydrothermally grown between the MoS2 / RGO substrate sheets. The NiCo2O4 core-shell structure has a large available surface area and is suitable for supercapacitor electrode materials.
[0046] In this example, the electrochemical properties of GO, MoS2 / RGO and NiCo2O4@MoS2 / RGO electrode materials were investigated respectively, and the investigation method is as follows:
[0047] In this example, the electrochemical properties of the electrode material were investigated by specific capacitance testing.
[0048] Figure 4 The electrochemical test results of NiCo2O4@MoS2 / RGO electrode material are shown in the figure. It can be seen from the figure that compared with GO and MoS2 / RGO, NiCo2O4@MoS2 / RGO electrode has the longest discharge time. -1When the specific capacitance of GO, MoS2 / RGO and NiCo2O4@MoS2 / RGO electrodes is 88 F g -1 , 442F g -1 ,946Fg -1 , the specific capacitance is increased to 946F g -1 This is because the synergistic effect among MoS2, RGO and NiCo2O4 leads to a significant improvement in the chemical properties, which plays a key role in the enrichment of the electrochemical activity of NiCo2O4@MoS2 / RGO.
[0049] Embodiment 2:
[0050] (1) Preparation of GO:
[0051] Add 240mL of concentrated H2SO4 and 20mL of H3PO4 into the reactor and stir for 20min to mix evenly. Then add 1g of graphite powder and add 8g of KMnO4 in batches. Stir and react for 24h in an ice-water bath. After the reaction, add 300mL of deionized water below 5°C to the reaction solution and then add 0.06mol of H2O2. The color of the reaction solution instantly turns yellow-brown and a precipitate is obtained. Wash with distilled water and freeze-dry for 10h to obtain GO.
[0052] (2) Preparation of MoS2 / RGO:
[0053] 0.04 g GO was ultrasonically dispersed in 80 mL deionized water, and then an aqueous solution containing 5 mmol sodium tetrapropylene benzene sulfonate, 3 mmol MoO3 and 0.5 mmol KSCN were added thereto and stirred for 20 min. Then, in a high-pressure reactor, the mixed solution was reacted at 240 ° C for 26 h to obtain a precipitate. The precipitate was then washed with deionized water and freeze-dried for 10 h to obtain MoS2 / RGO.
[0054] (3) Preparation of MnCo2O4@MoS2 / RGO electrode materials:
[0055] 100 mg MoS2 / RGO was ultrasonically dispersed in 100 mL deionized water, and then 4 mmol Mn(NO)2·6H2O, 5 mmol Co(NO)3·6H2O, 10 g d-glucose and 9.5 mmol urea were added thereto in sequence. After stirring and mixing evenly, the mixture was hydrothermally reacted at 240 °C for 24 h. After the reaction, a precipitate was obtained, which was washed and dried to obtain MnCo2O4@MoS2 / RGO electrode material.
[0056] In this example, the electrochemical properties of GO, MoS2 / RGO and MnCo2O4@MoS2 / RGO electrode materials were investigated respectively, and the investigation method is as follows:
[0057] In this example, the electrochemical performance of the electrode material was investigated by specific capacitance test. -1 When the specific capacitance of GO, MoS2 / RGO and MnCo2O4@MoS2 / RGO electrodes is 94 F g -1 , 412F g -1 ,738F g -1 , the specific capacitance is increased to 738F g -1 This is because the synergistic effect between MoS2, RGO and MnCo2O4 leads to a significant improvement in chemical properties.
[0058] Embodiment 3:
[0059] (1) Preparation of GO:
[0060] Add 180mL of concentrated H2SO4 and 20mL of H3PO4 into the reactor and stir for 20min to mix evenly. Then add 1.5g of graphite powder and add 7.5g of KMnO4 in batches. Stir and react for 24h in an ice-water bath. After the reaction, add 200mL of deionized water below 5°C to the reaction solution and then add 0.01mol of H2O2. The color of the reaction solution instantly turns yellow-brown and a precipitate is obtained. Wash with distilled water and freeze-dry for 10h to obtain GO.
[0061] (2) Preparation of MoS2 / RGO:
[0062] 10 mg of GO was ultrasonically dispersed in 40 mL of deionized water, and then an aqueous solution containing 3 mmol of sodium diisooctyl sulfosuccinate, 1.5 mmol of MoO3 and 0.4 mmol of KSCN were added thereto and stirred for 20 min. Then, in a high-pressure reactor, the mixed solution was reacted at 190 ° C for 16 h to obtain a precipitate. The precipitate was then washed with deionized water and freeze-dried for 10 h to obtain MoS2 / RGO.
[0063] (3) Preparation of MgCo2O4@MoS2 / RGO electrode materials:
[0064] 10 mg MoS2 / RGO was ultrasonically dispersed in 50 mL deionized water, and then 1 mmol Mg(NO)2·6H2O, 1 mmol Co(NO)3·6H2O, 1 g d-glucose and 3.5 mmol urea were added thereto in sequence. After stirring and mixing evenly, the mixture was hydrothermally reacted at 190 °C for 12 h. After the reaction, a precipitate was obtained, which was washed and dried to obtain MgCo2O4@MoS2 / RGO electrode material.
[0065] In this example, the electrochemical properties of GO, MoS2 / RGO and MgCo2O4@MoS2 / RGO electrode materials were investigated respectively, and the investigation method is as follows:
[0066] In this example, the electrochemical performance of the electrode material was investigated by specific capacitance test. -1 When the specific capacitance of GO, MoS2 / RGO and MgCo2O4@MoS2 / RGO electrodes is 84 F g -1 , 212F g -1 , 437F g -1 , the specific capacitance is increased to 437F g -1 This is because the synergistic effect between MoS2, RGO and MgCo2O4 leads to a significant improvement in chemical properties.
[0067] Embodiment 4:
[0068] (1) Preparation of GO:
[0069] Add 220mL of concentrated H2SO4 and 20mL of H3PO4 into the reactor and stir for 20min to mix evenly. Then add 2g of graphite powder and add 12g of KMnO4 in batches. Stir and react for 24h in an ice-water bath. After the reaction, add 240mL of deionized water below 5°C to the reaction solution and then add 0.015mol of H2O2. The color of the reaction solution instantly turns yellow-brown and a precipitate is obtained. Wash with distilled water and freeze-dry for 10h to obtain GO.
[0070] (2) Preparation of MoS2 / RGO:
[0071] Take 25 mg of GO and ultrasonically disperse it in 70 mL of deionized water. Then, add an aqueous solution containing 3.5 mmol of sodium dibutylnaphthalenesulfonate, 1.8 mmol of MoO3 and 0.45 mmol of KSCN and stir for 20 min. Then, in a high-pressure reactor, react the mixed solution at 200 ° C for 24 h to obtain a precipitate. The precipitate is then washed with deionized water and freeze-dried for 10 h to obtain MoS2 / RGO.
[0072] (3) Preparation of CuCo2O4@MoS2 / RGO electrode materials:
[0073] 30 mg MoS2 / RGO was ultrasonically dispersed in 70 mL deionized water, and then 2.8 mmol Cu(NO)2·6H2O, 2.6 mmol Co(NO)3·6H2O, 8 g d-glucose and 7.2 mmol urea were added thereto in sequence. After stirring and mixing evenly, the mixture was hydrothermally reacted at 200 °C for 20 h. After the reaction, a precipitate was obtained, which was washed and dried to obtain CuCo2O4@MoS2 / RGO electrode material.
[0074] In this example, the electrochemical properties of GO, MoS2 / RGO and CuCo2O4@MoS2 / RGO electrode materials were investigated respectively, and the investigation method is as follows:
[0075] In this example, the electrochemical performance of the electrode material was investigated by specific capacitance test. -1 When the specific capacitance of GO, MoS2 / RGO and CuCo2O4@MoS2 / RGO electrodes is 93 F g -1 , 434F g -1 , 844F g -1 , the specific capacitance is increased to 946F g -1 This is because the synergistic effect between MoS2, RGO and CuCo2O4 leads to a significant improvement in chemical properties.
[0076] Embodiment 5:
[0077] (1) Preparation of GO:
[0078] Add 240mL of concentrated H2SO4 and 20mL of H3PO4 into the reactor and stir for 20min to mix evenly. Then add 2g of graphite powder and add 10g of KMnO4 in batches. Stir and react for 24h in an ice-water bath. After the reaction, add 260mL of deionized water below 5°C to the reaction solution and then add 0.02mol of H2O2. The color of the reaction solution instantly turns yellow-brown and a precipitate is obtained. Wash with distilled water and freeze-dry for 10h to obtain GO.
[0079] (2) Preparation of MoS2 / RGO:
[0080] 15 mg of GO was ultrasonically dispersed in 65 mL of deionized water, and then an aqueous solution containing 3 mmol of sodium dodecylbenzene sulfonate, 2.3 mmol of MoO3 and 0.46 mmol of KSCN were added thereto and stirred for 20 min. Then, in a high-pressure reactor, the mixed solution was reacted at 200 °C for 24 h to obtain a precipitate, which was then washed with deionized water and freeze-dried for 10 h to obtain MoS2 / RGO.
[0081] (3) Preparation of FeCo2O4@MoS2 / RGO electrode materials:
[0082] 40 mg MoS2 / RGO was ultrasonically dispersed in 70 mL deionized water, and then 3.2 mmol Fe(NO)2·6H2O, 2.6 mmol Co(NO)3·6H2O, 7.5 g d-glucose and 6.1 mmol urea were added thereto in sequence. After stirring and mixing evenly, the mixture was hydrothermally reacted at 200 °C for 24 h. After the reaction, a precipitate was obtained, which was washed and dried to obtain FeCo2O4@MoS2 / RGO electrode material.
[0083] In this example, the electrochemical properties of GO, MoS2 / RGO and FeCo2O4@MoS2 / RGO electrode materials were investigated respectively, and the investigation method is as follows:
[0084] In this example, the electrochemical performance of the electrode material was investigated by specific capacitance test. -1 When the specific capacitance of GO, MoS2 / RGO and FeCo2O4@MoS2 / RGO electrodes is 95 F g -1 , 398F g -1 , 637F g -1 , the specific capacitance is increased to 637F g -1 This is because the synergistic effect between MoS2, RGO and FeCo2O4 leads to a significant improvement in chemical properties.
[0085] Embodiment 6:
[0086] (1) Preparation of GO:
[0087] Add 210mL of concentrated H2SO4 and 20mL of H3PO4 into the reactor and stir for 20min to mix evenly. Then add 1.5g of graphite powder and add 7g of KMnO4 in batches. Stir and react for 24h in an ice-water bath. After the reaction, add 200mL of deionized water below 5°C to the reaction solution and then add 0.03mol of H2O2. The color of the reaction solution instantly turns yellow-brown and a precipitate is obtained. Wash with distilled water and freeze-dry for 10h to obtain GO.
[0088] (2) Preparation of MoS2 / RGO:
[0089] 22 mg of GO was ultrasonically dispersed in 70 mL of deionized water, and then an aqueous solution containing 3 mmol of sodium dodecylbenzene sulfonate, 2.5 mmol of MoO3 and 0.4 mmol of KSCN were added thereto and stirred for 20 min. Then, in a high-pressure reactor, the mixed solution was reacted at 220 °C for 20 h to obtain a precipitate. The precipitate was then washed with deionized water and freeze-dried for 10 h to obtain MoS2 / RGO.
[0090] (3) Preparation of ZnCo2O4@MoS2 / RGO electrode materials:
[0091] 30 mg MoS2 / RGO was ultrasonically dispersed in 70 mL deionized water, and then 3.2 mmol Zn(NO)2·6H2O, 4.2 mmol Co(NO)3·6H2O, 8.8 g d-glucose and 7.9 mmol urea were added thereto in sequence. After stirring and mixing evenly, the mixture was hydrothermally reacted at 220 °C for 20 h. After the reaction, a precipitate was obtained, which was washed and dried to obtain ZnCo2O4@MoS2 / RGO electrode material.
[0092] In this example, the electrochemical properties of GO, MoS2 / RGO and ZnCo2O4@MoS2 / RGO electrode materials were investigated respectively, and the investigation method is as follows:
[0093] In this example, the electrochemical performance of the electrode material was investigated by specific capacitance test. -1 When the specific capacitance of GO, MoS2 / RGO and ZnCo2O4@MoS2 / RGO electrodes is 92 F g -1 , 453F g -1 , 870F g -1 , the specific capacitance is increased to 870F g -1 This is because the synergistic effect between MoS2, RGO and ZnCo2O4 leads to a significant improvement in chemical properties.
[0094] In summary, the present invention uses MoS2 composite graphene, and MoS2 is intercalated between graphene sheets to reduce graphene agglomeration and increase the specific surface area of the material. At the same time, the hydrothermal growth method is used to hydrothermally synthesize "sesame ball"-shaped NiCo2O4 core-shell microspheres on the MoS2 / RGO substrate. Due to the introduction of NiCo2O4 core-shell microspheres, not only the electrochemical performance of the composite material is improved, but also the stacking phenomenon of the MoS2 / RGO substrate is reduced. The "sesame ball"-shaped NiCo2O4@MoS2 / RGO electrode material prepared by this method has a large effective contact area with the electrolyte, a small ion resistance, is conducive to the transmission and storage of charges, and improves the energy storage capacity of the material.
[0095] The embodiments are preferred implementations of the present invention, but the present invention is not limited to the above-mentioned implementations. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essential content of the present invention belong to the protection scope of the present invention.
Claims
1. A method for preparing MCo2O4@MoS2 / RGO electrode material, characterized in that: include: (1) Preparation of MoS2 / RGO: GO was ultrasonically dispersed in deionized water, and then a surfactant aqueous solution, MoO3 and KSCN were added thereto, and the mixture was stirred and evenly mixed before a hydrothermal reaction was performed. After the reaction was completed, a precipitate was obtained, which was washed and dried to obtain MoS2 / RGO; (2) Preparation of MCo2O4@MoS2 / RGO electrode materials: MoS2 / RGO was dispersed in deionized water, and then nitrate, Co(NO)3•6H2O, d-glucose and urea were added in sequence, stirred and mixed evenly, and then subjected to hydrothermal reaction. After the reaction, a precipitate was obtained, which was washed and dried to obtain MCo2O4@MoS2 / RGO electrode material.
2. The method for preparing the MCo2O4@MoS2 / RGO electrode material according to claim 1, characterized in that: The preparation method of GO comprises: Concentrated H2SO4 and H3PO4 were stirred and mixed evenly, graphite powder was added and mixed evenly, and then KMnO4 was added in batches. The reaction was stirred under ice-water bath conditions. After the reaction was completed, a reaction solution was obtained. Deionized water and H2O2 were added to the reaction solution. The reaction solution turned yellow-brown and a precipitate was obtained. The precipitate was washed and dried to obtain GO.
3. The method for preparing the MCo2O4@MoS2 / RGO electrode material according to claim 1, characterized in that: In step (1), the dosage ratio of GO, deionized water, surfactant, MoO3 and KSCN is 0.01~0.04g:40~80mL:3~5mmol:1.5~3mmol:0.4~0.5mmol; The hydrothermal reaction conditions are 190-240° C. for 16-26 hours.
4. The method for preparing the MCo2O4@MoS2 / RGO electrode material according to claim 3, characterized in that: The surfactant includes any one of sodium dodecylbenzene sulfonate, sodium tetrapropylenebenzene sulfonate, sodium diisooctyl sulfosuccinate, and sodium dibutylnaphthalene sulfonate.
5. The method for preparing the MCo2O4@MoS2 / RGO electrode material according to claim 1, characterized in that: In step (2), the amount ratio of MoS2 / RGO, deionized water, nitrate, Co(NO)3•6H2O, d-glucose and urea is: 10~100mg: 50~100mL: 1~4mmol: 1~5mmol: 1~10g: 3.5~9.5mmol; The hydrothermal reaction conditions are 190-240° C. for 12-24 hours.
6. The method for preparing the MCo2O4@MoS2 / RGO electrode material according to claim 5, characterized in that: The nitrate includes any one of Mn(NO)2•6H2O, Ni(NO)2•6H2O, Mg(NO)2•6H2O, Cu(NO)2•6H2O, and Zn(NO)2•6H2O.
7. The MCo2O4@MoS2 / RGO electrode material prepared by the method according to any one of claims 1 to 6, characterized in that: In the MCo2O4@MoS2 / RGO electrode material, MoS2 / RGO is used as a substrate, and core-shell MCo2O4 nano-microspheres are in situ synthesized on the MoS2 / RGO substrate; in the MCo2O4@MoS2 / RGO electrode material, MoS2 nanoflowers grow between RGO sheets, and core-shell MCo2O4 nano-microspheres are uniformly dispersed between MoS2 / RGO sheets; M in the core-shell MCo2O4 includes any one of Mn, Ni, Mg, Cu, and Zn.
8. The MCo2O4@MoS2 / RGO electrode material according to claim 7, characterized in that When core-shell MCo2O4 nanospheres are in situ synthesized on MoS2 / RGO, part of the MoS2 is redistributed on the surface of the MCo2O4 nanospheres, making the MCo2O4@MoS2 / RGO electrode material sesame-shaped.
9. Use of the MCo2O4@MoS2 / RGO electrode material according to claim 7 in the preparation of supercapacitors.
10. Use of the MCo2O4@MoS2 / RGO electrode material according to claim 7 in micro-nanoelectronic devices, solar cell electrodes, photoelectric converters, and transparent conductive films.